Enzymatic Hydrolysis of Alkaline Pretreated Coconut Coir - Akbarningrum Fatmawati; Rudy Agustriyanto; Yusnita Liasari (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2013)
The purpose of this research is to study the effect of concentration and temperature on the cellulose and lignin content, and the reducing sugars produced in the enzymatic hydrolysis of coconut coir. In this research, the coconut coir is pretreated using 3%, 7%, and 11% NaOH solution at 60oC, 80oC, and 100oC. The pretreated coir were assayed by measuring the amount of cellulose and lignin and then hydrolysed using Celluclast and Novozyme 188 under various temperature (30oC, 40oC, 50oC) and pH (3, 4, 5). The hydrolysis results were assayed for the reducing sugar content. The results showed that the alkaline delignification was effective to reduce lignin and to increase the cellulose content of the coir. The best delignification condition was observed at 11% NaOH solution and 100oC which removed 14,53% of lignin and increased the cellulose content up to 50,23%. The best condition of the enzymatic hydrolysis was obtained at 50oC and pH 4 which produced 7,57 gr/L reducing sugar. © 2013 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)